Absorptive Capacity for Need Knowledge: Antecedents and Effects for Employee Innovativeness - Tim G. Schweisfurth; Christina Raasch (Research Policy, 2018)
Innovation occurs when knowledge about unmet customer needs intersects with knowledge about technological solutions. Both knowledge types are often located outside the firm and need to be absorbed in order for innovation to occur. While there has been extensive research into absorptive capacity for solution knowledge, a necessary complement – absorptive capacity for new customer needs – has been neglected. In an individual-level study of 864 employees from a home appliance firm, we show that need absorptive capacity is theoretically and empirically distinct from solution absorptive capacity, and that both are positively associated with employee innovativeness. Interestingly, we find asymmetric extra-domain effects: prior solution knowledge is positively related to need absorptive capacity (cross-pollination effect), while prior need knowledge is negatively related to solution absorptive capacity (attenuation effect). We contrast the cognitive underpinnings of the two absorptive capacity types, contributing to emerging scholarly thinking on the domain-specificity and micro foundations of absorptive capacity.
Keywords: 330